A Semi-analytical Calculation Method for Time-varying Meshing Stiffness and Transmission Error of Spiral Bevel Gear - Liao Ping; Wei Jing; Zhang Aiqiang; Zhang Weiqing (Jixie chuandong)
The traditional method of calculating time-varying meshing stiffness of spiral bevel gears mostly adopted finite element static analysis method, but it needed to be calculated many times, also the single tooth meshing stiffness calculated by the mean value of the node elastic deformation has a large error. For this reason, a calculation method for time-varying meshing stiffness of spiral bevel gear is improved. The meshing stiffness of single node was introduced into the traditional calculation method, and the meshing stiffness of each node on the working tooth surface is superimposed to obtain single tooth meshing stiffness, the calculation accuracy is higher. The time-varying meshing stiffness and transmission error of spiral bevel gears are calculated based on explicit dynamic finite element analysis. The calculation time period is reduced by calculating once without repeating multiple finite element analysis. The variation law of time-varying meshing stiffness and transmission error under different load torques is researched. Also the influence of two contact parameters such as contact ellipse axis length and contact path direction on time-varying meshing stiffness and transmission error are analyzed. The research results show that the time-varying meshing stiffness and transmission error increase with the increase of load torque, but the peak-to-peak value of time-varying meshing stiffness and transmission error decrease with the increase of load torque. The time-varying meshing stiffness and the peak-to-peak value of transmission error (PPTE) are improved with the increase of contact ellipse long axis length. As the contact path increase, the time-varying meshing stiffness has a sudden increase, and the transmission error changes little.